Diagnostic accuracy of wrist MRI in comparison to wrist arthroscopy regarding TFCC lesions in clinical practice: handsurgery - Spies, Christian; Unglaub, Frank; Bruckner, Thomas; Müller, Lars Peter; Eysel, Peer; Rau, Johannes (Archives of orthopaedic and trauma surgery, 2022)
The purpose of this study was to arthroscopically verify MRI diagnostic accuracy for triangular fibrocartilage complex (TFCC) lesions in a regular clinical environment.
Gesehen am 11.03.2024